Acquisition of specific antibodies and their influence on cell-mediated immune response in neonatal cord blood after maternal pertussis vaccination during pregnancy. Issue 19 (1st May 2019) - Lima, Laila; Molina, Mariela da Gama Fortunato; Pereira, Beatriz Sena; Nadaf, Marvin Lucas Ale; Nadaf, Maria Isabel Valdomir; Takano, Olga Akiko; Carneiro-Sampaio, Magda; Palmeira, Patricia
Highlights: This report is the first to describe Tdap responsiveness in pregnant women in Brazil. Tdap vaccine increases pertussis-specific IgG in both maternal and newborn serum. The best placental transfer ratios were achieved in women immunized in gestation weeks 26–31. Anti-Bp and anti-PT IgA levels in colostrum were not affected by vaccine status. Tdap maternal vaccination doesn't affect the neonatal cell-mediated immune response. Abstract: Maternal immunization with pertussis acellular vaccine (Tdap) is an intervention that provides protection to newborns. However, it has been reported that high maternal antibody levels may adversely affect the immune response of infants after active immunization. In this study, we evaluated neonatal passive acquisition of pertussis-specific antibodies and their influence on the neonatal cell-mediated immune response. Pregnant women were either vaccinated with Tdap vaccine (case group, n = 66) or received no vaccine (control group, n = 101). Whole-cell Bordetella pertussis (Bp), pertussis toxin (PT), filamentous hemagglutinin (FHA) and pertactin (PRN)-specific serum IgG were quantified in paired maternal-cord sera, and Bp- and PT-specific IgA were evaluated in colostrum by ELISA. Ex vivo neonatal blood lymphocyte responsiveness after Bp stimulation was assessed in case (n = 17) and control (n = 15) groups using flow cytometry to detect proliferation, cytokine production and activation phenotype of lymphocytes in the context of high specific IgG acquired after maternal vaccination. Anti-Bp, PT, FHA and PRN IgG concentrations in maternal and cord sera from case group were higher than those in control group with positive correlation indexes in both groups for all pertussis antigens. The control group presented higher placental transfer ratios of specific antibodies and, in the case group, vaccination between 26 and 31 gestation weeks was associated with the best placental transfer ratios. Specific IgA concentrations in colostrum were not affected by vaccine status. Whole blood assays revealed that newborns responded to Bp stimulation with higher expression of CD40L, CD69 and CD4 + T cell proliferation compared to unstimulated cells, and a lower Th1 response, while a preserved Th2 response compared to adults, but there were no differences between the neonatal groups for any of the studied parameters. Our results indicate that higher pertussis-specific IgG levels in newborn sera after maternal vaccination do not affect the neonatal ex vivo cell-mediated immune response.